Multi-Walled Carbon Nanotubes Accelerate Leukaemia Development in a Mouse Model - Qingqing Wang; Jingdan Han; Mujia Wei; Huikai Miao; Min Zhang; Biao Wu; Yao Chen; Yanwen Zheng; Robert Peter Gale; Bin Yin (Toxics)
Inflammation is associated with an increased risk of developing various cancers in both animals and humans, primarily solid tumors but also myeloproliferative neoplasms (MPNs), myelodysplastic syndromes (MDS), and acute myeloid leukemia (AML). Multi-walled carbon nanotubes (MWCNTs), a type of carbon nanotubes (CNTs) increasingly used in medical research and other fields, are leading to a rising human exposure. Our study demonstrated that exposing mice to MWCNTs accelerated the progression of spontaneous MOL4070LTR virus-induced leukemia. Additionally, similar exposures elevated pro-inflammatory cytokines such as interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α and induced reactive oxygen species (ROS) in a murine macrophage cell line. These effects were significantly reduced in immunodeficient mice and when mice were treated with methoxypolyethylene glycol amine (PEG)-modified MWCNTs. These findings underscore the necessity of evaluating the safety of MWCNTs, particularly for those with hematologic cancers.